Efficiency in Health Care Sector in Tamil Nadu (India): An Exploratory Analysis - Purohit BC (Online Journal of Health & Allied Sciences, 2016)
Keeping in view the importance of efficiency in resource utilization in healthcare sector, we focus on efficiency of health care system at sub-state level (i.e., district level) in India using Tamil Nadu state and its district level data for 2012-13. It being an economically advanced state, in terms of Infant Mortality Rate (IMR) the state ranks second lowest among the Indian states. We explore the reasons for relative performance of different districts with Data Envelopment Analysis. We used IMR as output variables. Using Principal component analysis we tried a sub-set of variables which had low correlations. Thus three components with an Eigen value greater than one were used. These related to Total beds in ESI (Employees state Insurance scheme) hospitals, Population per doctor of PHPM (Public Health and Preventive Medicine) and Full Vaccination. The factor scores for these components were used for Data Envelopment Analysis (DEA). We have focused on CCR scores (or constant returns to scale technical efficiency, CRST score) and efficiency rankings based on these are discussed. Thus our results pertaining to district level health system efficiency for Tamil Nadu state indicate that some of the districts have low efficiency in utilization of inputs like doctors and beds. There are also other districts which need more of these inputs which may enhance their output and efficiency. Thus it suggests that that the lowest performance of Kancheepuram district, for instance, is mainly owing to low availability of these health inputs as well as partly due to less efficient utilisation of inputs. It is also inferred that higher efficiency of Chennai is due to better availability of hospital beds and doctors per population. Among the factors external to health system, the statistical significance of an improved source of drinking water indicates that supportive input of better potable water supply helps to improve in general health status and thus reduce inter-district disparities in health system efficiency. Overall, thus, there is a mix of both inefficiency and inadequacy of inputs which has increased the inter district disparities in health outcomes in the state.